Experiences in the development of a Smart Lab. (13th August 2009) - Nugent, C.D.; Mulvenna, M.D.; Hong, X.; Devlin, S.
There is now a growing demand to provide improved delivery of health and social care due to changes in the age profile of our population. One area where these services may be improved is through the development of smart living environments. Within this paper we provide an overview of the drivers behind the development of such environments along with details of the different ways in which they may exist. Finally, we provide details of our initial experiences in the establishment of a Smart Living Environment for the development of assistive technologies to support independent living.